Curcumin in Alzheimer's disease: Can we think to new strategies and perspectives for this molecule?. (October 2017) - Serafini, Melania Maria; Catanzaro, Michele; Rosini, Michela; Racchi, Marco; Lanni, Cristina
Graphical abstract: Abstract: Population aging is an irreversible global trend with economic and socio-political consequences. One of the most invalidating outcomes of aging in the elderly is cognitive decline, leading to dementia and often related to neurodegenerative disorders. Among these latter, Alzheimer's disease (AD) is the major cause of dementia, affecting more than 30 million of individuals worldwide. To date, the treatment of AD remains a challenge because of an incomplete understanding of the events that lead to the selective neurodegeneration typical of Alzheimer's brains. There is an enormous global demand for new effective therapies and researchers are investigating new fields. One promising strategy is the use of nutraceuticals as integrative, complementary and preventive therapy. Curcumin is one example of natural product with anti-AD properties, with promising potential for prevention, treatment and diagnostic. The limitations in the use of curcumin as therapeutic are represented by its pharmacokinetics profile and the low bioavailability after oral administration. However, curcumin has been the focus of intense research for new drug development. Here we analyzed some new approaches that have been applied in the attempt to improve its use, particularly new formulations, changes in the way of administration, nanotechnology-based delivery systems and the hybridization strategy.